Characterizing serotonin expression throughout bovine mammary gland developmental stages and its relationship with 17β-estradiol at puberty - Sena L. Field; Lisa M. Arendt; Laura L. Hernandez; Jimena Laporta (PLoS ONE, 2025)
Serotonin acts in an autocrine/paracrine manner within the mammary epithelium regulating cell homeostasis during lactation and cell turnover during involution after milk stasis. However, the presence and role of mammary serotonin during the pubertal developmental stage is unknown in the bovine. Here, we characterized the serotonin receptor profile and serotonin immunolocalization in bovine mammary tissue at eight developmental stages (i.e., birth, weaning, puberty, six months gestation, early lactation, mid-lactation, early dry and late dry, n = 6/stage). Further, we investigated the effects of 5-HTP (serotonin precursor), 17β-estradiol (E2), and ICI 182780 (ERα antagonist) either alone or in various combinations (i.e., 5-HTP +  E2, 5-HTP + ICI, E2 + ICI or 5-HTP + E2 +  ICI) on cultured bovine mammary epithelial cells (MAC-T). Serotonin receptor gene expression is highly dynamic throughout mammary development, particularly highly expressed in the puberty stage expressing 12 out of the 13 serotonin receptors evaluated (5-HTR1A, -1B, -1D, -1F, -2A, -2B, -2C, -3B, -4, -5a, -6, and -7), relative to the birth stage. Following a 24-hour incubation, all treatments except ICI increased MAC-T cell proliferation. Incubation with 5-HTP +  ICI resulted in a downregulation of ESR1, ESR2, GPER1 and AREG, relative to CON. Incubation with 5-HTP and E2 alone downregulated the expression of TPH1, 5-HTR1A and 5-HTR1B, relative to CON. Overall, our data indicates serotonin is present in the juvenile developing mammary tissue and the expression of various receptors is observed suggesting an active involvement at this early stage. Additionally, serotonin might indirectly regulate mammary epithelial cell proliferation alone and concurrently with E2 during puberty through the modulation of E2 signaling genes and 5-HTR1A and -1B.